STRUCTURE OPTIMIZATION OF ELECTRIC AUTOMOBILE TRANSMISSION HOUSING - ZHENG SongLin; QU JinQian; SHI WenShan; CHEN YouSong; LIU Hui; XU Ying (Jixie qiangdu)
Troubleshooting,finite element analysis and structure optimization were carried out through 7 Diamonds analysis in view of electric automobile transmission housing crack. First, problems of manufacturing were found by 7 Diamonds troubleshooting; Then FEA of the transmission housing before optimization was implemented by Hyperworks 11. 0,proving the validity of cracking reason; Thirdly,3 structure aspects of transmission housing were optimized,then FEA of the transmission housing after optimization was carried,the stress distribution cloud image shows that the maximum stress reduces greatly and this conforms to the requirements of the strength; Finally,on the bench test 6 tests were verified,the results indicates that the optimization of transmission housing meets intensity and durability requirements and optimization scheme is feasible. So the method of structure optimization to solve the problem of housing cracking through 7 Diamonds analysis has significance in engineering project.